Penggunaan e-modul Berbasis Isu Sosio-saintifik Dalam Upaya Meningkatkan Keterampilan Argumentasi dan Pengambilan Keputusan Siswa SMA - Ghaida Sekarlita Fadha; Widi Purwianingsih; Rini Solihat (Postgraduate, University of Mataram, 2023)
The use of e-modules based on socio-scientific issues can be used as a way to provide argumentation and decision-making skills. This study aims to determine the use of e-modules based on socio-scientific issues in improving the argumentation and decision-making skills of high school students. This study used a quasi-experimental method. The research design used was the non-equivalent control group design. The sample in this study was class X students consisting of 132 people who were determined by purposive sampling technique. The research was conducted on two classes, namely the experimental class (learning using e-modules based on socio-scientific issues) and the control class (learning using modules not based on socio-scientific issues). The results showed that there was a significant difference in the mean between the experimental class and the control class in argumentation skills. The Mann-Whitney test on the value of argumentation skills shows a number (2-tailed = 0.000) < Î± (0.05) which means that there is a difference in the effectiveness of using socio-scientific issue-based e-modules with ordinary modules to improve students' argumentation skills. Then the results of the study showed that there was a significant difference in the average between the experimental class and the control class in student decision-making, shows that the Mann-Whitney test score on the value of argumentation skills shows the number (2-tailed = 0.000) < Î± (0.05) which means that there is a difference in the effectiveness of using socio-scientific issue-based e-modules with regular modules to improve student decision making. As for the criteria for the N-Gain score, the use of e-modules based on socio-scientific issues to improve students' argumentation skills is included in the moderate category (N-gain = 0.42), and the use of e-modules based on socio-scientific issues to improve student decision making is included in the medium category (N-gain = 0.56).